Spatiotemporal evolution of time-lagged vegetation responses to moisture conditions and the influencing factors in a highly human-impacted area in China - Yuxing Yan; Guoqiang Wang; Yinglan A; Xiaojing Zhang; Baolin Xue; Jin Wu; Yuntao Wang (Ecological Informatics)
The interactions between vegetation growth and moisture conditions are critical indicators of vegetation resistance to water stress. However, existing studies have largely overlooked the cumulative and time-lagged effects of vegetation responses to moisture changes. It remains unclear whether vegetation–moisture interactions remain stable and sustainable under intensive human activity. In this study, the optimal response timescale (TSd) was the standardized precipitation–evapotranspiration index timescale (1–24 months), which exhibited the greatest correlation with the normalized difference vegetation index. The vegetation–moisture interaction (Rd) was the corresponding correlation coefficient. These metrics were analyzed over the past four decades in a highly human-impacted area, the Inner Mongolia Reach of the Yellow River Basin. The differences in TSd and Rd were compared across regions with different human activity intensity changes. The possible drivers were examined through the random forest method. The results revealed that TSd significantly increased in the study area between 1982 and 2021 (0.338 months yr−1), suggesting that vegetation was more susceptible to prolonged moisture conditions. The Rd under the TSd increased overall (0.00595 yr−1), exhibiting a pronounced increase in areas where human activity intensity increased significantly, despite the initially low correlations, indicating that human interventions could have enhanced the capacity of vegetation to utilize moisture conditions. Additionally, the climatic factors of temperature and radiation variability were the primary determinants of TSd and Rd, respectively. However, the population significantly influenced the Rd trends. Our results highlighted the critical role of climate change in regulating the interactions between vegetation growth and moisture conditions. Furthermore, the influences of human activities on the stability of vegetation–moisture interactions could not be overlooked. These findings could enhance our understanding of long-term vegetation–moisture interactions and provide a basis for ecological conservation and management efforts in the Inner Mongolia Reach of the Yellow River Basin.